Temporal signals in dairy cattle slurry and fertilized field soil resistomes and bacterial communities - Williams, Alexander D.; Hooton, Stephen P. T.; King, Elizabeth; Avery, Lisa M.; Hough, Rupert L.; Hobman, Jon L.; Stekel, Dov J.; Neal, Andrew L.; West, Helen M. (Frontiers in Microbiology, 2026)
IntroductionDairy cattle waste is a globally significant source of organic fertilizer which contains a cocktail of microbes and antibiotic resistance genes (ARGs). These ARGs may present a risk to human and animal health, yet there is still limited farm-system-level understanding of how long-term and multiple slurry applications alter field soil resistomes and total microbial communities.MethodsUsing metagenomics, we assessed both immediate and longer-term changes in grassland field soil resistomes and bacterial communities over a year of routine cattle slurry application.ResultsOur findings suggest that soil microbial communities are resilient to bacteria and ARGs introduced via slurry, even after repeated applications. Most slurry-borne ARGs were not enriched in field soil, however, those common in soil, such as rifamycin resistance genes, were consistently elevated relative to field soil with no history of slurry application. We observed transient increases in slurry-associated macrolide-lincosamide-streptogramin ARGs, however, their persistence appeared to be influenced by timing of slurry application. Similar transient effects were shown by the recovery of a high quality, slurry-associated Proteiniphilum spp. metagenome assembled genome (MAG).DiscussionWe show that MAGs represent a powerful tool for examining the transfer of slurry-borne microorganisms, as they can be more characteristic of these environments than typical sentinel organisms which are easily cultivated. Our findings indicate that while the soil bacterial community shows considerable resilience to slurry-borne bacteria and ARGs, this may be diminished by temporal factors that remain largely unexplored and poorly understood. This is important because resilience inferred from short-term observations may not fully capture delayed or transient responses, potentially leading to underestimation of the persistence of slurry-borne bacteria and ARGs.